Study on Roof-Coal Caving Characteristics with Complicated Structure by Fully Mechanized Caving Mining - Yunpei Liang; Lei Li; Xuelong Li; Kequan Wang; Jinhua Chen; Zhongguang Sun; Xuelin Yang (Shock and Vibration)
With mining technology and mechanization degree being improving, fully mechanized caving mining technology (FCM) has become a main method for thick coal seam extraction in China. However, roof-coal caving characteristics in turn restrict its recovery efficiency, especially for the coal seam with complicated structure (CCS), that is, the coal seam comprises hard or soft coal and gangue. In order to explore the key factors influencing the roof-coal caving and recovery characteristics, related research work has been conducted as follows: firstly, a mechanical model of CCS has been established, which indicates the strength of the coal and gangue will directly affect the roof-coal recovery. Meanwhile, based on the geological settings of Qinyuan coal mine, numerical simulation on roof-coal caving law under different thicknesses of hard or soft coal and gangue has been performed using UDEC software. The results show that the maximum principal stress will increase with the increase of mining depth, making the roof-coal to break easily. Furthermore, the range of the plastic zone of the top coal and the damage degree of the top coal increase with the increase of mining depth. Physical modeling results show that when an extraction-caving ratio is 1, the number of times the coal arch forms is 0.43 at every caving, up to a maximum of 3; the number of times coal arch forms with an extraction-caving ratio of 2 is 4.65 times larger than that with an extraction-caving ratio of 1. The probability of coal arch formation with an extraction-caving ratio of 3 is minimal, about 0.4, which is due to that the arch span is large and the curvature is small, so it is difficult to form a stable arch structure. According to the mechanical characteristics of roof-coal in Qinyuan coal mine, deep-hole blasting technique has been used to reduce the fragments of roof-coal crushed. The results show that this technique can effectively improve the recovery of roof-coal.